2008
DOI: 10.1080/09064710701464719
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic content in cuttings of two clones of hybrid chestnut (Castaneacrenata×Castaneasativa) in the first days after cutting severance

Abstract: In this experiment, we studied the possible involvement of various phenolic acids in the rooting process of two chestnut hybrid clones (Marsol and Maraval Castanea crenata )C. sativa). The phenolic acids were measured in the cutting bases (root emergence zone) and in the cutting leaves. In the cutting bases, several hydroxycinnamic acids (caffeic, sinapic, ferulic and p-coumaric acid), chlorogenic and ellagic acids were observed, whereas in the cutting leaves only chlorogenic and ellagic acid were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…In V. davidii and V. kiusiana cuttings, no significant increase in IAA levels was found despite the fact that phenol levels increased during the 60 days after planting. Overaccumulation of hydroxycinnamic acids such as chlorogenic acid and ferulic acid was observed in the cuttings of chestnut clone with low rooting ability in the period of four days after planting, while the concentration of these acids was decreased in the clone with higher rooting ability [39]. This observation and our results suggest that accumulated phenols during planting of cuttings act as an inhibitor rather than an inducer of rooting via the prevention of IAA oxidation.…”
Section: Discussionsupporting
confidence: 72%
“…In V. davidii and V. kiusiana cuttings, no significant increase in IAA levels was found despite the fact that phenol levels increased during the 60 days after planting. Overaccumulation of hydroxycinnamic acids such as chlorogenic acid and ferulic acid was observed in the cuttings of chestnut clone with low rooting ability in the period of four days after planting, while the concentration of these acids was decreased in the clone with higher rooting ability [39]. This observation and our results suggest that accumulated phenols during planting of cuttings act as an inhibitor rather than an inducer of rooting via the prevention of IAA oxidation.…”
Section: Discussionsupporting
confidence: 72%
“…In agreement with the present results, Tombesi et al [50] reported that the part of the mother shoot used for cuttings affected their rooting ability and is closely related to carbohydrate accumulation, in particular to soluble sugar content, at the cutting's base during the rooting process. This is also the case for PA, and phenolic compounds [24,36,51], because their high endogenous content has been correlated with high rooting percentages in olive cuttings [21] and in various other tree species [52,53].…”
Section: Discussionmentioning
confidence: 88%
“…Tyrosol, luteolin-7-glucoside and rutin, as well as total o-diphenols, which are considered to act protectively against indole-3-acetic acid catabolism, protecting it from oxidation, during the induction and initiation phases [24,35,36], were found, based on the PCA results (Table 6), to be related with the increased rooting performance of the girdled cuttings. These results indicate the possible positive effect of specific phenolic compounds on the adventitious rooting process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different biochemical compounds may trigger various regulatory mechanisms in woody plants. Osterc et al (2008) reported higher content levels of various polyphenolic compounds in chestnut cuttings and linked them to a better rooting potential. The type of a regulatory mechanism of the specific compound depends on the type of function which this compound has in a plant.…”
Section: Discussionmentioning
confidence: 96%